Moral Beauty During the COVID-19 Pandemic: Prosocial Behavior Among Adolescents and the Inspiring Role of the Media. (March 2023) - de Leeuw, Rebecca N. H.; van Woudenberg, Thabo J.; Green, Kayla H.; Sweijen, Sophie W.; van de Groep, Suzanne; Kleemans, Mariska; Tamboer, Sanne L.; Crone, Eveline A.; Buijzen, Moniek
In this study, we examined whether adolescents helped others during the COVID-19 pandemic and how stories in the media inspired them in doing so. Using an online daily diary design, 481 younger adolescents ( M  = 15.29, SD  = 1.76) and 404 older adolescents ( M  = 21.48, SD  = 1.91) were followed for 2 weeks. Findings from linear mixed effects models demonstrated that feelings of being moved by stories in the media were related to giving emotional support to family and friends, and to helping others, including strangers. Exposure to COVID-19 news and information was found to spark efforts to support and help as well and keeping physical distance in line with the advised protective behaviors against COVID-19. Moreover, helping others was related to increased happiness. Overall, the findings of this study highlight the potential role of the media in connecting people in times of crisis.